The Influence of Location, Store Atmosphere, and Shopping Experience on Revisit Intention at Shelters Coffee in Kayu Aro - Budaya, Indra; Fatmasari, Dewi Kayanti (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This article discusses the influence of three main factors location, store atmosphere, and customer experience on revisit intention at Shelters Coffee located in Kayu Aro. In the context of the increasingly competitive café industry, where each café is vying to attract and retain visitors, it is important for café owners to understand the factors that influence customers' decisions to return. This study uses a quantitative approach with a survey method, involving 80 respondents selected through purposive sampling, to analyze the relationship between these factors and revisit intention. The analysis results show that the café's strategic location and a pleasant customer experience have a positive and significant influence on customers' intention to revisit. This indicates that consumers are more likely to visit a café that is easily accessible and provides a satisfying experience during their visit. On the other hand, the store atmosphere, while important for creating comfort, does not show a significant impact on revisit intention according to the findings of this study. These findings provide valuable insights for café owners to develop more targeted marketing and management strategies, focusing on improving location and customer experience as top priorities. Meanwhile, although store atmosphere did not show significant impact in this study, it may still be considered as a supporting factor that needs further attention, especially in creating an atmosphere that supports customer comfort and long-term loyalty. Overall, this study highlights the importance of managing factors that can enhance the customer experience to increase a café's chances of retaining customer loyalty in a highly competitive market